SANKSI HUKUM TERHADAP ANGGOTA POLISI YANG MELAKUKAN PENYALAHGUNAAN NARKOTIKA DI INDONESIA: SANKSI HUKUM TERHADAP ANGGOTA POLISI YANG MELAKUKAN PENYALAHGUNAAN NARKOTIKA DI INDONESIA - Idayana Putri, Siti; M Syahrul Borman; Nur Handayati; Vieta Imelda Cornelis (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Members of the police who commit criminal acts of narcotics abuse in the Indonesian NationalPolice need special attention, they cannot be said to be ordinary things, but law enforcement must be strict.If the enemy in the police force continues to exist, the eradication of narcotics crimes will not be maximized,bearing in mind that Law Number 35 of 2009 concerning Narcotics stipulates that in addition toinvestigators from the National Narcotics Agency (BNN), Indonesian National Police investigators havethe authority to conduct investigations into criminal acts. narcotics and illicit drug trafficking. The mainproblems that will be discussed in writing this thesis are how to enforce the law against members of thepolice who abuse narcotics and what are the legal sanctions against members of the police who commitnarcotics abuse. In this study, the Statute Approach was used, carried out by examining all laws andregulations that are related to the legal issues being handled. And the conceptual approach (ConceptualApproach), moving from the views and doctrines that developed in the science of lawKeywords: Legal Sanctions, Police Members, Narcotics Abuse